Quantification of beta glucans and phenolic compounds present in extract of Lion’s Mane mushroom (Hericium erinaceus) from Brazil. - Cruz, David Lucas Nunes de Souza; Faria, Carolina Pereira de Morais; Bach, Erna Elisabeth (Periódicos Brasil. Pesquisa Científica, 2026)
The Lion’s Mane mushroom (Hericium erinaceus) is an edible basidiomycete with recognized medicinal properties, including anticancer, neuroprotective, and immunomodulatory effects. It contains biological and bioactive compounds such as beta-glucans, phenolic compounds, proteins, and terpenoids. This study focuses on the extraction and quantification of beta-glucans and phenolic compounds from H. erinaceus cultivated in Brazil using aqueous extraction methods. The results demonstrate that increasing water temperature above 90°C enhances the concentration of beta-glucans and proteins, confirming greater solubility. All extracts presented phenolic compounds as chlorogenic acid, caffeic acid, ferulic acid, p-coumaric acid and kaempferol that are important to maintain the antioxidant effect. Ethanol precipitation (up to 20%) effectively separates bioactive compounds, highlighting differences in extracted phenolic concentrations. The findings emphasize the need for tailored extraction techniques depending on the intended application, whether for food, pharmaceutical, or medicinal purposes.